THE EFFECT OF FACILITIES ON CUSTOMER SATISFACTION AT SATRIA FUTSAL NATAR DISTRICT - Miranda Ariyanti; Vonny Tiara Narundana (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to find out about the significant influence of facilities on customer satisfaction. The researcher implemented a quantitative type method with 200 populations and 133 samples obtained through the Purposive Sampling Technique. The researcher used a simple linear regression test using a hypothesis test, namely the t-test. This research results in a positive influence of facilities on customer satisfaction. Furthermore, with the overall influence of facilities on customer satisfaction, which is 68% while the remaining 32% is influenced by other variables. If the service business, especially Satria Futsal, pays attention to both the completeness and comfort of the facilities directly and indirectly, then this can cause a sense of satisfaction from customers.